Interreligious friendship after Nostra aetate - Fredericks, James L. (James Lee), 1951-; Sayuki Tiemeier, Tracy, 1975- (New York Palgrave Macmillan, 2014)
"Bringing together top Catholic theologians in the fields of interreligious dialogue and comparative theology, the book explores the ways in which personal relationships and the 'dialogue of life' are essential for theology. Here, Catholic theologians tell the personal stories of their interreligious friendships and explore the significance of their friendships for their own life and work, filling a major hole in theological endeavors. Comparative and interreligious theologies have positioned themselves as more concrete and engaged alternatives to the theology of religions, a field that articulates a theological system for understanding religions other than one's own. Yet, comparative theology has been reserved for a select few specialists, while academic interreligious dialogue all too often focuses on the theologies and practices of religions without engaging people concretely in their lives. "--
"In the 50 years since Vatican II's Declaration on the Relation of the Church to Non-Christian Religions (Nostra Aetate), Catholics across the globe have entered into extraordinary friendships with those who follow other religious paths. This volume celebrates these interreligious friendships by letting Catholics, sometimes together with their friends, tell their stories"--
Machine generated contents note: -- Introduction; James L. Fredericks -- 1. Learning in the Presence of the Other: My Friendship with Sara Lee; Mary C. Boys -- 2. Michael Signer and the Language of Friendship; John C. Cavadini -- 3.The Blessing of Sitting Together; Elena Procario-Foley -- 4. Faith and Friendship; David Burrell -- 5. Friendship: Cultivating Theological Virtue; Marianne Farina and Massarat Khan -- 6. Ties that Bind: Interfaith Friend, Interfaith Kin; Rita George-Tvrtkovic -- 7. Rasoul, My Friend and Brother; Bradley J. Malkovsky -- 8. Study and Friendship: Intersections throughout an Academic Life; Francis X. Clooney -- 9. Jivanmukti, Freedom, and a Cassette Recorder: Friendship beyond Friendship in the Tradition of Advaita Vedanta; Reid B. Locklin -- 10. Toddlers and Teas: Parenting in a Multireligious World; -- Tracy Sayuki Tiemeier and Mughda Yeolekar -- 11. With New Eyes to See: Changing the Perception of Self and Other through Interreligious Friendship; Karen B. Enriquez -- 12. Masao Abe: A Spiritual Friendship; James L. Fredericks -- 13. A Friend and Scholar: A Guide on the Way to Understanding Buddhism; Peter C. Phan -- 14. My Friendship with Rita Gross; Rosemary Radford Ruether -- 15. Interreligious Friendship: A Path to Conversion for a Catholic Theologian; SimonMary Asese Aihiokhai -- 16. Interreligious Friendship: Symbiosis of Human Relationship Vis-à-vis Religious Differences - A Christian Encounter with Two African Traditional Religionists; Marinus Chijioke Iwuchukwu -- Conclusion; Mary Margaret Funk.
Includes index.
Keywords: Catholic Church -- Relations; Christianity and other religions; Friendship -- Religious aspects; Interpersonal relations -- Religious aspects; RELIGION / Christianity / Catholic; RELIGION / Comparative Religion; SOCIAL SCIENCE / Sociology of Religion